Analysis of the use of media resulting from bioconversion of organic waste in the production of maggots BSF (black soldier fly) - syahrizal, Syahrizal; Ediwarman; Safratilofa; Ridwan, Muhamat (Indonesian Society of Scientific Aquaculture (ISSA), 2022)
Maggots is an organism derived from the eggs of the black fly, Hermentia illucens (black soldier fly, BSF), which undergoes metamorphosis in the second phase after the egg phase and before the pupa phase which then turns into an adult fly. The purpose of this study was to analyze the utilization of organic waste substrate on the production of BSF maggots cultivation. This research was conducted outdoor at the Freshwater Aquaculture Fisheries Center (BPBAT) Sungai Gelam Jambi with a completely randomized design (CRD) with 4 treatments and 3 replications; Treatment A: PKM (palm kernel meal) 100%, B (PKM 50% + cabbage vegetable waste 50%), C (PKM 50% + coconut pulp 50%) and D (PKM 50% + coconut pulp 25% + vegetable waste cabbage 25%). The average yield parameter of high maggots biomass in treatment A was 673.67 g/4 kg substrate and the lowest biomass in treatment D was 239.67 g/4 kg substrate. For the average weight and length of the best maggots in treatment A (0.20 g/individual) and (1.83 cm), the lowest was in B (0.12 g/Ind. and 1.58 cm). The highest was in treatment B (5,182.31 individual/4 kg substrate) and the lowest was in D (1,479.44 ind./4 kg substrate. The highest bioconversion value of maggots to organic matter OSE (organic substrate efficiency) was highest in treatment A (16, 84%) and the lowest was in D (5.99%). Technically, treatment A was slightly better than B, while economically the best organic substrate medium for maggots cultivation was in treatment B with a production cost of Rp. 7.257 and the ECR (economic conversion ratio) value of 5.81 was lower than the other 3 treatments. Keywords: Maggots, black soldier fly, Hermentia illucens, organic waste. ABSTRAK Maggots merupakan organisme yang berasal dari telur seranga lalat hitam, Hermentia illucens (black soldier fly, BSF). Tujuan penelitian ini yaitu menganalisis pemanfaatan subtrat limbah organik terhadap produksi budidaya maggots BSF. Penelitian ini dilaksanakan di Balai Perikanan Budidaya Air Tawar (BPBAT) Sungai Gelam, Jambi dengan rancangan acak lengkap (RAL) 4 perlakuan 3 ulangan yaitu perlakuan A : PKM (palm kernel meal) 100%, B (PKM 50% + limbah sayur kol 50%), C (PKM 50% + ampas kelapa 50%), dan D (PKM 50% + ampas kelapa 25%+ limbah sayur kol 25%).Rata-rata biomassa tertinggi didapatkan pada perlakuanA (673,67g/4 kg subtrat) dan biomassa terendah dihasilkan pada perlakuan D (239.67g/4 kg subtrat). Untuk bobot rata-rata dan panjang maggots terbaik dihasilkan pada perlakuan A (0,20 g/individu dan 1,83 cm/individu), terendah pada B (0,12 g/individu dan (1,58 cm). Jumlah populasi maggots yang terbanyak dihasilkan pada perlakuan B (5.182,31 ind./4 kg subtrat) dan terendah pada D (1.479,44 individu/4 kg subtrat). Nilai biokonversi maggots terhadap bahan organik OSEterbaik (organic substrate efficiency) tertinggi pada perlakuan A (16,84%) dan terendah pada D (5,99%). Secara teknis perlakuan A sedikit lebih baik dari B sedangkan secara ekonomi media subtrat organik terbaik untuk budidaya maggots terdapat pada perlakuan B dengan biaya produksi sebesar Rp. 7.257 dan nilai ECR (economic convertion ratio) sebesar 5.81 lebih rendah dari ke 3 perlakuan lainnya. Kata kunci: Maggots, black soldier fly, Hermentia illucens, limbah organik.